Robot-Assisted in Hip and Knee Surgery: Are we ready? - Sholahuddin Rhatomy,MD; Krisna Yuarno Phatama; Asep Santoso; Kukuh Dwiputra Hernugrahanto; Nicolaas Budhiparama (Indonesian Hip and Knee Society (IHKS), 2021)
The word 'robot' is derived from the Polish word